2020
DOI: 10.1155/2020/3463287
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Impact of Different Periodic Functions on Short-Term Freeway Travel Time Prediction Approaches

Abstract: Freeway travel time prediction is a key technology of Intelligent Transportation Systems (ITS). Many scholars have found that periodic function plays a positive role in improving the prediction accuracy of travel time prediction models. However, very few studies have comprehensively evaluated the impacts of different periodic functions on statistical and machine learning models. In this paper, our primary objective is to evaluate the performance of the six commonly used multistep ahead travel time prediction m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…Only 20 lags at maximum, less than 2 h for 5 min interval prediction, were introduced. It is observed that the traffic condition has cyclic patterns, and it has been confirmed that considering the cyclic pattern helps improve the prediction accuracy [62], [63]. Fourth, the implementation of multitask learning would improve the prediction accuracy.…”
Section: Discussionmentioning
confidence: 84%
“…Only 20 lags at maximum, less than 2 h for 5 min interval prediction, were introduced. It is observed that the traffic condition has cyclic patterns, and it has been confirmed that considering the cyclic pattern helps improve the prediction accuracy [62], [63]. Fourth, the implementation of multitask learning would improve the prediction accuracy.…”
Section: Discussionmentioning
confidence: 84%
“…Chen et al [21] established an ensemble machine-learning algorithm for the short-term traffic flow prediction via the integration of gradient boosting regression trees and the least absolute shrinkage and selection operator. Besides, Yang et al [23] and Miao et al [24] focus on predicting the traffic speed and travel time of the freeways by periodic function to improve the performance of the machine-learning models.…”
Section: Machine Learning Based Methodsmentioning
confidence: 99%
“…The study in [8] combines different statistical methods and machine learning methods with a trigonometric regression function to predict the evolution of the traffic speed. The previous study is extended in [9] by combining different statistical and machine learning methods with different periodic functions. Traffic predictions using data from fixed traffic detectors are restricted to the location of the detectors.…”
Section: Related Workmentioning
confidence: 99%
“…Three channels correspond to the spatiotemporal evolution of the three fundamental traffic variables estimated using FCD, and the three other channels to the spatiotemporal evolution of the three fundamental traffic variables estimated using data from the induction loops. When the traffic is predicted using FCD, the images have three channels, a width of 72 pixels and a height of 95 pixels since the freeway is divided into 95 sections 9 . The 72 pixels for the width represent the temporal evolution of a traffic variable for the previous 3.6 hours.…”
Section: B Neural Network For Traffic Predictionmentioning
confidence: 99%